2013
DOI: 10.18564/jasss.2178
|View full text |Cite
|
Sign up to set email alerts
|

Put Your Money Where Your Mouth Is: DIAL, A Dialogical Model for Opinion Dynamics

Abstract: We present DIAL, a model of group dynamics and opinion dynamics. It features dialogues, in which agents gamble about reputation points. Intra-group radicalisation of opinions appears to be an emergent phenomenon. We position this model within the theoretical literature on opinion dynamics and social influence. Moreover, we investigate the effect of argumentation on group structure by simulation experiments. We compare runs of the model with varying influence of the outcome of debates on the reputation of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Similarly, Granovetter’s model of threshold behavior (Granovetter, 1978) and subsequent developments (e.g., Watts, 1999, 2002) showed that, when individuals make binary decisions, such as signing a declaration of war, evading taxes, or reporting bullying by a supervisor within a workplace, nonlinear interaction effects can result in unpredictable social outcomes, especially when individuals are sensitive to behavior of others and are embedded in social network structures. In the same vein, Deffuant, Amblard, Weisbuch, and Faure (2002) and Hegselmann and Krause (2002) examined the role of social influence on opinion distribution and dynamics and showed that societies can converge toward polarized or pluriform collective opinions (Huet, Deffuant, & Jager, 2008; Jager & Amblard, 2004), minority positions may become dominant (Galam, 2002), and reputable leaders emerge as a result of social interaction (Dykstra, Elsenbroich, Jager, Renardel de Lavalette, & Verbrugge, 2013). These social simulation studies show that large-scale societal changes may originate from many micro-level interactions and that even unique historic events with significant societal consequences can be partly explained in terms of complex social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Granovetter’s model of threshold behavior (Granovetter, 1978) and subsequent developments (e.g., Watts, 1999, 2002) showed that, when individuals make binary decisions, such as signing a declaration of war, evading taxes, or reporting bullying by a supervisor within a workplace, nonlinear interaction effects can result in unpredictable social outcomes, especially when individuals are sensitive to behavior of others and are embedded in social network structures. In the same vein, Deffuant, Amblard, Weisbuch, and Faure (2002) and Hegselmann and Krause (2002) examined the role of social influence on opinion distribution and dynamics and showed that societies can converge toward polarized or pluriform collective opinions (Huet, Deffuant, & Jager, 2008; Jager & Amblard, 2004), minority positions may become dominant (Galam, 2002), and reputable leaders emerge as a result of social interaction (Dykstra, Elsenbroich, Jager, Renardel de Lavalette, & Verbrugge, 2013). These social simulation studies show that large-scale societal changes may originate from many micro-level interactions and that even unique historic events with significant societal consequences can be partly explained in terms of complex social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these models also assume bounded influence, which raises the question of how easily network connectivity alone can produce opinion divergence. Similarly, the DIAL model [56] provides means for isolating and segregating communities via a number of comparison and communication processes.…”
Section: Opinion Divergence and The Bounded Influence Conjecturementioning
confidence: 99%
“…For example, researchers have considered emotion [90,91]; social network connections [92,93]; and argumentation and dialog [56]. In addition, a number of richer representations of opinion have been examined.…”
Section: Interim Summarymentioning
confidence: 99%
See 2 more Smart Citations